Electrical characterization of Au/3C-SiC/n-Si/Al Schottky junction - Chung, G. S.; Kim, K. S.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2010)
High temperature silicon carbide Schottky diode was fabricated with Au deposited on poly 3C-SiC thin film grown on n-type Si(100) using atmospheric pressure chemical vapor deposition. The charge transport mechanism of the diode was studied in the temperature range of 300-550 K. The forward and reverse bias currents of the diode increase strongly with temperature and the diode shows a non-ideal behavior due to the series resistance and the interface states associated with 3C-SiC. The charge transport mechanism is a temperature activated process, in which, the electrons passes over of the low barriers and in turn, the diode has a large ideality factor. The electrical parameters of the Au/3C-SiC/n-Si/Al Schottky diode were explained on the basis of the thermionic emission theory with double Gaussian distribution of the barrier heights due to the barrier height inhomogeneities at metal/semiconductor interface. The interface state density of the diode was determined by the conductance-frequency method and it was of order of 9.18 x 10(10) eV(-1) cm(-2). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 3C-SiC diode; Schottky diode; Interfacial state density